Study of structural-mechanical properties of the ointment base - V. V. Rudenko (Zaporožskij Medicinskij Žurnal)
The ENTRY. For the local treatment of surgical wounds basis of a medicine plays an important role in ensuring its therapeutic effect. Ointment framework depends on adequate frequency of applications, pharmacokinetics, therapeutic effect and absence/presence of side effects. Unjustifiable selected the basis of a medicinal product may cause not only the increase or reduction of the actions of the active substance, but also a total absence of it.